Functionalized core/shell nanofibers for the differentiation of mesenchymal stem cells for vascular tissue engineering - Ezhilarasu, H.; Sadiq, A.; Ratheesh, G.; Sridhar, S.; Ramakrishna, Seeram; Mohd Hasbi, Ab. Rahim; M. M., Yusoff; Rajan, Jose; Venugopal, Jayarama Reddy (Future Medicine Ltd., 2019)
Aim: Atherosclerosis is a common cardiovascular disease causing medical problems globally leading to coronary artery bypass surgery. The present study is to fabricate core/shell nanofibers to encapsulate VEGF for the differentiation of mesenchymal stem cells (MSCs) into smooth muscle cells to develop vascular grafts. Materials & methods: The fabricated core/shell nanofibers contained polycaprolactone/gelatin as the shell, and silk fibroin/VEGF as the core materials. Results: The results observed that the core/shell nanofibers interact to differentiate MSCs into smooth muscle cells by the expression of vascular smooth muscle cell (VSMC) contractile proteins α-actinin, myosin and F-actin. Conclusion: The functionalized polycaprolactone/gelatin/silk fibroin/VEGF (250 ng) core/shell nanofibers were fabricated for the controlled release of VEGF in a persistent manner for the differentiation of MSCs into smooth muscle cells for vascular tissue engineering.